THE POTENTIAL OF INDIGENOUS BACTERIA FOR REMOVING CADMIUM FROM INDUSTRIAL WASTEWATER IN LAWANG, EAST JAVA - Pambudiono, Agung; Suarsini, Endang; Amin, Mohamad (Journal of Tropical Life Science, 2018)
Heavy metals have been used in various areas around the world especially in the industrial sector. Heavy metals contamination is very dangerous for ecosystem because of its toxicity for some organisms. Cadmium (Cd) is a dangerous metal pollutant that can cause remarkable diverse of toxic effects, in particular for humans and animals. The use of bacteria as bioremediation agents has been widely studied because more efficient, less cost, and environmentally friendly strategy. This present study aimed to isolate and identify Cd-resistant bacteria from the industrial disposal site. Wastewater samples were collected from disposal site of agar flour industry in Lawang Malang, East Java. The collected wastewater effluent was analyzed for physicochemical properties. Isolation of Cd-resistant bacteria was carried out using serial dilution. Bacterial isolates were observed and tested for their effects on the content of Cd. The content of Cd was tested daily using Atomic Absorption Spectroscopy (AAS) for seven consecutive days. Data was analyzed using one-way ANOVA (p < 0.05) and Tukey test. Characterization of potential bacterium was performed using bacterial identification kit. Four bacteria isolates have been successfully isolated from the wastewater sample. There was a statistically significant difference between groups as determined by one-way ANOVA (F = 1229.62, p = 0.00). A Tukey post hoc test revealed that all conditions are significantly different from each other. The content of Cd in wastewater sample was statistically significantly lower after taking the A isolate (3.39 mg/L, p = 0.00), B Isolate (1.47 mg/L, p = 0.00), C Isolate (1.15 mg/L, p = 0.00), and D isolate (1.95 mg/L, p = 0.00) compared to the control treatment (5.11 mg/L, p = 0.00). Two of the most potential isolates identified as Pseudomonas flourescens (C isolate) and Enterobacter agglomerans (B isolate).